Diagnosis of monoclonal gammopathy of renal significance - Bridoux, Frank; Leung, Nelson; Hutchison, Colin A.; Touchard, Guy; Sethi, Sanjeev; Fermand, Jean-Paul; Picken, Maria M.; Herrera, Guillermo A.; Kastritis, Efstathios; Merlini, Giampaolo; Roussel, Murielle; Fervenza, Fernando C.; et al. (Kidney international, 2015)
Monoclonal gammopathy of renal significance (MGRS) regroups all renal disorders caused by a monoclonal immunoglobulin (MIg) secreted by a nonmalignant B-cell clone. By definition, patients with MGRS do not meet the criteria for overt multiple myeloma/B-cell proliferation, and the hematologic disorder is generally consistent with monoclonal gammopathy of undetermined significance (MGUS). However, MGRS is associated with high morbidity due to the severity of renal and sometimes systemic lesions induced by the MIg. Early recognition is crucial, as suppression of MIg secretion by chemotherapy often improves outcomes. The spectrum of renal diseases in MGRS is wide, including old entities such as AL amyloidosis and newly described lesions, particularly proliferative glomerulonephritis with monoclonal Ig deposits and C3 glomerulopathy with monoclonal gammopathy. Kidney biopsy is indicated in most cases to determine the exact lesion associated with MGRS and evaluate its severity. Diagnosis requires integration of morphologic alterations by light microscopy, immunofluorescence (IF), electron microscopy, and in some cases by IF staining for Ig isotypes, immunoelectron microscopy, and proteomic analysis. Complete hematologic workup with serum and urine protein electrophoresis, immunofixation, and serum-free light-chain assay is required. This review addresses the pathologic and clinical features of MGRS lesions, indications of renal biopsy, and a proposed algorithm for the hematologic workup.